Relationship between Working Capital and Cash Lines Affects the Profit of Vietnam Securities Company - Tran Van Hai, (International Journal of Scientific Research and Management (IJSRM), 2021)
Studying the relationship between working capital and cash flow affecting profitability of Vietnamese securities companies, through tobit model presented in the form of two-dimensional panel data: time dimension (from 2012 to 2019), the space dimension is the enterprise (48 securities companies), corresponding to 370 observations, using STATA 14 software to verify and estimate the tobit model. As a result, the relationship between working capital and cash flow (available cash flow) significantly affects the profitability of Vietnamese securities companies, Average collection period (ACP) has a negative relationship with ROE/ROA, while Average Payout Period (APP) has no significant effect on ROE/ROA. The implication is that securities companies can increase the profitability of the business by shortening the cash conversion cycle, shortening the receivable collection period, that is, for securities companies with positive cash flows, investment should be reduced. working capital to increase profitability.